Experimental study and improvement on tribological behaviors of automotive lubricants with dilution of various gasoline-bioethanol blends / Leang So Khuong - Leang, So Khuong (2017)
Concerns over depleting fossil fuel reserves and climate change have resulted in stringent legislation demanding automobiles use more renewable fuels in particular bioethanol, which is being considered as a long-term gasoline replacement. However, the piston ring and cylinder wall interface, which is the largest contributor to engine friction, suffers the highest levels of fuel dilution into the lubricant from unburned fuel, especially bioethanol that has high heat of vaporization to enhance the tendency of fuel dilution in the crankcase. Recently, bioethanol is blended with gasoline at increasingly higher concentrations and the accumulation of fuel in the crankcase is significant. Therefore, it is crucial to study the effect of various bioethanol-gasoline blends on properties degradation and tribological characteristics of engine oil as well as improving friction and wear behaviors of bioethanol-diluted engine oil. This research provides insight into using higher bioethanol blend and bioethanol-resistance lubricant formulation. In this study, three objectives were achieved to understand properties degradation and tribological behaviors and improvement of lubricant with bioethanol dilution. In the first study, five bioethanol-gasoline blends are formulated, namely, pure gasoline (E0), and gasoline blended with ethanol at different percentage volumes (10, 20, 30 and 85%, designated as E10, E20, E30, and E85, respectively). These fuels are then blended with synthetic oil (SO) at a dilution rate of 6 vol.%. These fuel-oil mixtures were then tested in four-ball wear tester according to ASTM D4172 standard test. The four-ball machine enables to investigate friction and wear of bioethanol-diluted oils. The second objective was carried out for the purpose of improving friction and wear losses from bioethanol-diluted oils, the nanocomposite of tungsten disulfide and graphene (GP/WS2) was added to the fuel-oil blends as an antiwear additive at three concentrations of 0.01wt%, 0.02wt%, and 0.04wt%, respectively, and tested using the same conditions. The third objective aims to observe the combined effect of ta-C coating and antiwear additive (GP/WS2) on tribological behavior of bioethanol-diluted engine oil under boundary lubrication using high frequency reciprocating ring (HFRR). The result shows that the addition of gasoline-bioethanol blend decreases the oil viscosity, and increases the acidity of the oil because bioethanol is more acidic in nature compared to gasoline. All fuel-diluted oil samples have higher friction and wear losses, compared to the fresh synthetic oil. After adding the additive, the result reveals that GP/WS2 performs lower friction and wear in all blends, compared to bioethanol-diluted oils without additive. The wear losses reduce with the increase of nanocomposite concentrations from 0.01%-0.04wt%. It is shown that E10-SO and E20-SO need 0.01-0.02wt% GP/WS2 to improve wear performance to below baseline oil (SO). However, E30-SO and E85-SO performance lower friction and wear than pure SO when 0.04wt% GP/WS2 is dispersed to the blends. The combined effect of ta-C coating and GP/WS2 performs a significant reduction of friction and wear losses of bioethanol-diluted oil. From this study, it is suggested that 0.01%-0.02wt%. GP/WS2 should be added to commercial engine oil used with the bioethanol-fueled engine to improve the lubricating efficiency of the engine and hamper the effect of bioethanol dilution on engine oil.